Answer:
C
Explanation:
Given the two functions, we need to find
(g ° f)(4)
This means, we need to put the function f(x) INTO the function g(x) and then evaluate that new function at x = 4.
We put the whole expression of f(x) into "x" of g(x). Shown below:
![f(x)=x^2-3\\g(x)=(x+2)/(x)\\(gof)(x)=(x^2-3+2)/(x^2-3)\\(gof)(x)=(x^2-1)/(x^2-3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/fwtb5u7vtoeo3ltryn7aln5k6cx1t3px7j.png)
Now we plug in 4 into x and evaluate:
![(gof)(x)=(x^2-1)/(x^2-3)\\(gof)(4)=(4^2-1)/(4^2-3)\\(gof)(4)=(15)/(13)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/d58mpfjdp6gbmtkx7kd2gd9d8v0026ymp6.png)
Thus,
correct answer is C